2000
DOI: 10.1046/j.1365-2702.2000.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress amongst district nurses: a preliminary investigation

Abstract: This paper presents the results of a pilot study investigating stress among district nurses in the north-west of England. Nurses completed questionnaires covering job satisfaction, mental health, stress, Type A behaviour, health behavior, coping skills and demographic details. A specific measure of stress was developed following in-depth interviews with primary care professionals, including district nurses. A total of 79 district nurses took part in the study. The major sources of stress isolated by the distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 18 publications
3
48
0
4
Order By: Relevance
“…This has implications for nurses and especially for hospital as an organization. Those results are different from other studies that showed sources of stress such as dealing with life and death situations, caring for patients who make demands, and implementing proper treatments (Aurelio, 1993;Callagham, Tay-Ying, Wyatt, 2000;Rout, 2000). McVicar's literature review (2003) about workplace stress in nursing demonstrated that "workload, leadership/management style, professional conflict and emotional costs of caring have been the main sources for nurses."…”
Section: Discussionmentioning
confidence: 78%
“…This has implications for nurses and especially for hospital as an organization. Those results are different from other studies that showed sources of stress such as dealing with life and death situations, caring for patients who make demands, and implementing proper treatments (Aurelio, 1993;Callagham, Tay-Ying, Wyatt, 2000;Rout, 2000). McVicar's literature review (2003) about workplace stress in nursing demonstrated that "workload, leadership/management style, professional conflict and emotional costs of caring have been the main sources for nurses."…”
Section: Discussionmentioning
confidence: 78%
“…Stress from interactions with patients is salient in nurses’ lives 1015. For example, Mariam et al found in 2012 that 60.8% of female nurses reported that quick-tempered patients were a primary source of work-related stress 16.…”
Section: Nurses’ Relationships With Patientsmentioning
confidence: 99%
“…[56789] The stressors may be varied in number and type; nevertheless, one's physiological, psychological, and social makeup determines the attitudes associated with the stress, making it stimulating and exciting to some, whereas others may feel stressed and burned. [10]…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%